PENGARUH PARTISIPATIF ANGGARAN, KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL PT JASA MARGA Tbk - WUNER, DHANY RISCHARD; Subardjo, Anang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze and to test the participatory budgeting and organizational commitment to themanagerial performance. Meanwhile the sample is head of department and head of division who works at PTJasa Marga Tbk Surabaya. The data collection technique has been done by issuing questionnaires. The data isthe primary data which has been collected by sending questionnaires to respondents. The research approach isquantitative, whereas the analysis technique has been done by using multiple linear regression analysis. Theresult of the research of determination coefficient value is 32.2%, and each of the participatory budgetingvariable and organizational commitment variables has significant influence to the managerial performance.Meanwhile 67.8% disclosure of managerial performance can be explained by other variables outside the researchmodel. The result of hypothesis test concludes that participatory budgeting variable and organizationalcommitment variable have positively influence to the managerial performance.Keywords: Participatory Budgeting, Organizational Commitment, Managerial CommitmentABSTRAK